Conservation of the endangered Arctic fox in Norway - are successful reintroductions enough?. (November 2022) - Landa, Arild; Rød-Eriksen, Lars; Ulvund, Kristine R.; Jackson, Craig; Thierry, Anne-Mathilde; Flagstad, Øystein; Eide, Nina E.
Abstract: Translocation of captive-bred animals has become a widespread conservation practice to counteract species extinctions. We analyse and discuss the apparent success and shortcomings of Arctic fox ( Vulpes lagopus ) reintroductions in alpine tundra areas of Norway. We followed the fate of 915 foxes between 2007 and 2020 and estimated the apparent survival and reproductive success of captive-bred and released Arctic foxes, compared to wild-born descendants. Relationship to abundance of small rodents, population size, and age were explored. Overall, apparent survival and probability of breeding were similar between captive-bred and wild-born foxes, positively linked to rodent abundance. For wild-born foxes, both breeding propensity and litter size declined with increasing fox population size. This could be a first sign of the limited capacity of single tundra patches to house self-subsistent populations. Thus, facilitating and maintaining connectivity among remnant and re-established Arctic fox populations, creating functional metapopulations, is essential for further improvement and long-term survival. Relying on the combined measures of supplementary feeding and red-fox ( Vulpes vulpes ) control, the Arctic fox captive-breeding and reintroduction programme has so far been highly successful. However, anthropogenic drivers facilitating red fox invasion into the Arctic fox habitat, along with climate driven irregularities and dampened small rodent cycles, could inhibit the establishment of a self-sustained population. A more holistic ecosystem approach and conservation measures to restore alpine fauna should be considered. Highlights: Captive-bred Arctic foxes perform equally well as wild-born foxes in the wild. Obtaining metapopulation functionality appears pivotal for Arctic fox conservation. Rodent abundance is important in spite of supportive feeding. Climate driven irregularities and dampened rodent cycles challenge conservation goals. Red fox invasion into the Arctic fox habitat could be limited by ecosystem-based management.